Apartment Layout And Privacy Satisfaction - Wahid, Julaihi (2008)
Housing design has always been a crucial subject of architect’s concern. Architecture in general and housing design in particular has often been criticized by some architects and also in academic literature for not fulfilling people's needs and requirements.